AQAD PROGRAM BANTUAN DINAS PERTANIAN KELOMPOK TANI BAGI DALAM TINJUAN FIQH MUAMALAH (Studi di Jorong Bulan Sarik Nagari Sungai Jambu Kecamatan Pariangan Kabupaten Tanah Datar) - Silvia Nur Indah Sari; Farida Arianti (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The problem of this research is how the form of assistance at the Department of Agriculture is given to farmer groups, what type of contract is the provision of assistance to farmer groups. The purpose of this study was to identify and explain the form of assistance at the Department of Agriculture given to farmer groups, what types of contracts for providing assistance to farmer groups. The research method that the author uses is a qualitative research method using field research with observation and interview data collection techniques. Primary data sources consist of the head of the field extension, the village guardian, the head and members of the farmer group. The data processing carried out here is qualitative. Based on the results of the research that the author has done, the implementation of the provision of assistance in 2019, 2020, and 2019 from the Department of Agriculture to farmer groups in Jorong Bulan Sarik Nagari Sungai Jambu was carried out by handing over assistance provided in the form of freelance assistance which could be utilized by members and the head of the farmer group, the assistance is in the form of plant seeds and farming machinery. After the assistance is given, there is no form of return agreement with the Agriculture service or the village guardian. In the utilization of harvests from the assistance of the Department of Agriculture will also be enjoyed by farmer groups who receive the assistance. So the implementation of providing assistance to the group that occurs contains a halal element because there are no arguments that prohibit it.